A Retrospective Study on Genetic Heterogeneity within Treponema Strains: Subpopulations Are Genetically Distinct in a Limited Number of Positions. - Darina Čejková; Michal Strouhal; Steven J Norris; George M Weinstock; David Šmajs (Public Library of Science (PLoS), 2015)
Pathogenic uncultivable treponemes comprise human and animal pathogens including agents of syphilis, yaws, bejel, pinta, and venereal spirochetosis in rabbits and hares. A set of 10 treponemal genome sequences including those of 4 Treponema pallidum ssp. pallidum (TPA) strains (Nichols, DAL-1, Mexico A, SS14), 4 T. p. ssp. pertenue (TPE) strains (CDC-2, Gauthier, Samoa D, Fribourg-Blanc), 1 T. p. ssp. endemicum (TEN) strain (Bosnia A) and one strain (Cuniculi A) of Treponema paraluisleporidarum ecovar Cuniculus (TPLC) were examined with respect to the presence of nucleotide intrastrain heterogeneous sites.The number of identified intrastrain heterogeneous sites in individual genomes ranged between 0 and 7. Altogether, 23 intrastrain heterogeneous sites (in 17 genes) were found in 5 out of 10 investigated treponemal genomes including TPA strains Nichols (n = 5), DAL-1 (n = 4), and SS14 (n = 7), TPE strain Samoa D (n = 1), and TEN strain Bosnia A (n = 5). Although only one heterogeneous site was identified among 4 tested TPE strains, 16 such sites were identified among 4 TPA strains. Heterogeneous sites were mostly strain-specific and were identified in four tpr genes (tprC, GI, I, K), in genes involved in bacterial motility and chemotaxis (fliI, cheC-fliY), in genes involved in cell structure (murC), translation (prfA), general and DNA metabolism (putative SAM dependent methyltransferase, topA), and in seven hypothetical genes.Heterogeneous sites likely represent both the selection of adaptive changes during infection of the host as well as an ongoing diversifying evolutionary process.